Phenotypic and Genotypic Drug Susceptibility Assessment of Mycobacterium bovis Bacillus Calmette-Guérin Clinical Strains - Sisco, Maria Carolina (Infect Drug Resist, 2021)
PURPOSE: Mycobacterium bovis Bacillus Calmette-Guérin (BCG) is the only vaccine licensed against tuberculosis. Despite the protection offered by the vaccine, in some circumstances children and immunocompromised individuals can develop associated infections, known as BCGitis. Drug susceptibility patterns of BCG clinical strains have rarely been described. We aimed to describe the susceptibility pattern of BCG clinical strains isolated in two different countries. METHODS: We performed culture-based drug susceptibility testing of thirty one BCG strains isolated from patients in Brazil (n=5, 16%) and Argentina (n=26, 84%) using the broth micro-dilution method (phenotypic method). Final antibiotic concentrations for susceptibility testing ranged from 0.5 to 16 mg/L for amikacin, 0.3125 to 10 mg/L for ethambutol, 0.05 to 1.6 mg/L for isoniazid and 0.25 to 8 mg/L for rifampicin, streptomycin and ofloxacin. Additionally, we compared the results with genetic data obtained by whole genome sequencing. RESULTS: By using the phenotypic method we detected one strain resistant to ethambutol, three strains resistant to rifampicin and one resistant to isoniazid. Additionally, two strains that were phenotypically resistant to both isoniazid and rifampicin carried mutations in the katG and rpoB genes simultaneously. CONCLUSION: There is evidence of the emergence of BCG-resistant strains isolated from vaccine-related complications. We recommend drug susceptibility testing of the BCG strain causing the infection in order to prevent treatment failure.